2012
DOI: 10.1016/j.jaci.2012.01.060
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA signature in patients with eosinophilic esophagitis, reversibility with glucocorticoids, and assessment as disease biomarkers

Abstract: Background The role of microRNAs (miRNAs), a key class of regulators of mRNA expression and translation, in patients with eosinophilic esophagitis (EoE) has not been explored. Objective We aimed to identify miRNAs dysregulated in patients with EoE and assess the potential of these miRNAs as disease biomarkers. Methods Esophageal miRNA expression was profiled in patients with active EoE and those with glucocorticoid-induced disease remission. Expression profiles were compared with those of healthy control s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
152
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(164 citation statements)
references
References 62 publications
6
152
3
Order By: Relevance
“…41 These findings are not just of academic interest as miR-21 is upregulated in multiple human Th2-associated diseases including eosinophilic esophagitis, atopic dermatitis, and ulcerative colitis. [42][43][44] In addition, miR-21 has been reported to be upregulated in human airway epithelial cells in response to IL-13 treatment and suppresses TLR-2 signaling in an animal model of asthma. 45 AntagomiRs or anti-miRs are a class of chemically engineered nucleotides that silences miRNA expression in vitro and/or in vivo.…”
Section: Mir-21 Regulate Polarized Adaptive Immune Responses In Allermentioning
confidence: 99%
See 4 more Smart Citations
“…41 These findings are not just of academic interest as miR-21 is upregulated in multiple human Th2-associated diseases including eosinophilic esophagitis, atopic dermatitis, and ulcerative colitis. [42][43][44] In addition, miR-21 has been reported to be upregulated in human airway epithelial cells in response to IL-13 treatment and suppresses TLR-2 signaling in an animal model of asthma. 45 AntagomiRs or anti-miRs are a class of chemically engineered nucleotides that silences miRNA expression in vitro and/or in vivo.…”
Section: Mir-21 Regulate Polarized Adaptive Immune Responses In Allermentioning
confidence: 99%
“…Analysis of esophageal eosinophil level and a myriad of esophageal transcripts for correlation with miR-21 demonstrated impressive correlations of miR-21 with esophageal eosinophil count, cell-specific markers for eosinophils, and CCL-26 (eotaxin-3), which is functionally involved in eosinophil recruitment. 44,73 Both miR-146a and miR-146b have been found to be upregulated in patients with eosinophilic esophagitis. 44 A previous report by Lu et al found that miR-146a could selectively suppress Th1 responses.…”
Section: Eosinophilic Esophagitismentioning
confidence: 99%
See 3 more Smart Citations